GAMBARAN PENGETAHUAN IBU HAMIL TENTANG MANFAAT KOLOSTRUM PADA BAYI BARU LAHIR DI DESA AEK HARUAYA KECAMATAN PORTIBI KABUPATEN PADANG LAWAS UTARA TAHUN 2017 - MEILIA SINTYA MUTIARA POHAN (JURNAL ILMIAH MAKSITEK, 2019)
Data from the World Health Organization (WHO) shows that there are 170 million children who are malnourished throughout the world. As many as 3 million of them die every year due to malnutrition. The high infant mortality rate in the world can actually be avoided by breastfeeding.The results of research on colostrum administration conducted by Krista (2009) stated that there were still many mothers who lacked or knew enough about the importance of giving colostrum to newborns. Lack of knowledge and factors affecting the level of education so that this information is not conveyed properly.Based on a preliminary survey conducted in September-December in Aek Haruaya Village, Portibi Subdistrict, Padang Lawas Utara Regency in 2017 from the results of questions and answers on third trimester pregnant women who came to check their pregnancy, it was found that many mothers did not understand about the benefits of colostrum, because according to belief milk that comes out first dirty and can cause a disease if given to newborns.This type of research is descriptive and the population in this study were all pregnant women who came to Aek Haruaya Village, Portibi District, Padang Lawas Utara Regency in 2017 as many as 31 people. The sampling technique in this study is to use the Total Population.After conducting the research, the authors conclude: The level of knowledge of pregnant women based on the age of the majority of respondents is well-informed to pregnant women aged 20-35 years as many as 14 respondents (87.5%) and the minority is not present in pregnant women aged <20 years. .2. The level of maternal knowledge based on the education of the majority of respondents is knowledgeable enough with a secondary education background of 11 respondents (68%, 75) and a minority of respondents have no knowledge of either with a basic education background. 3. knowledge of pregnant women based on the work of the majority of respondents who do not work knowledgeable enough with as many as 9 respondents (56.25%) and minority of respondents who do not work well knowledgeable . 4. The level of knowledge of pregnant women about the benefits of colostrum in newborns based on information sources, the majority of respondents received information from the environment with enough knowledge as many as 11 respondents (68.75%) and less knowledgeable minorities obtained from the mass media as much as 1 respondent (8.33 %).